2018
DOI: 10.1155/2018/8363265
|View full text |Cite
|
Sign up to set email alerts
|

Total HLA Class I Antigen Loss with the Downregulation of Antigen-Processing Machinery Components in Two Newly Established Sarcomatoid Hepatocellular Carcinoma Cell Lines

Abstract: Limited information is currently available concerning HLA class I antigen abnormalities in sarcomatoid hepatocellular carcinoma (sHCC). Here, we have analyzed the growth characteristics and HLA class I antigen status of four sHCC cell lines (sHCC29, sHCC63, sHCC74, and SAR-HCV); the first three were newly established in this study. Among the four, sHCC29 showed the highest growth rate in vitro and tumorigenicity in NOD-SCID mice. Unlike sHCC74 and SAR-HCV, both sHCC29 and sHCC63 had no detectable surface HLA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Although the downregulation of pHLA presentation in tumor cells is well documented in many cancers, [42][43][44][45] whether HCC cells present pHLAs at sufficient levels to activate a CTL response is still under debate. [46][47][48][49] Recent studies by Dr Bertoletti's team demonstrated that HBV antigens could be presented by HCC cells despite these antigens not being detectable by IHC techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Although the downregulation of pHLA presentation in tumor cells is well documented in many cancers, [42][43][44][45] whether HCC cells present pHLAs at sufficient levels to activate a CTL response is still under debate. [46][47][48][49] Recent studies by Dr Bertoletti's team demonstrated that HBV antigens could be presented by HCC cells despite these antigens not being detectable by IHC techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The evasion can occur through various mechanisms, such as oncogenic changes induced by viruses that result in phenotypic alterations in HLA-DR; the absence of a receptor on natural killer cells that interacts with different HLA molecules, and the presence of heterogeneous cell populations within tumors that generate multiple variants with different HLA phenotypes ( 14 ). These mechanisms are relatively rare in benign tumors but can be highly efficient in promoting malignancies ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, considering the human leukocyte anKgen (HLA) [48][49][50] and B2M 51,52 genes, which encode proteins crucial for anKgen presentaKon process criKcal for acKvaKng T cells and iniKaKng an immune response against tumor cells. DysregulaKon or alteraKons in the expression of these HLA genes can impact the immune system's ability to recognize and eliminate cancer cells, directly influencing the success of ICIs 49,51 . In addiKon, validated HCC immune players, CD74 53,54 (Fig.…”
Section: Detec9ng Differen9ally Expressed Isoforms In Single-cell Lon...mentioning
confidence: 99%